Coexistence of Psoriasis Vulgaris and Systemic Lupus Erythematosus: A Rare Clinical Case - Earlia, Nanda; Zulfan, Zulfan; Pradistha, Aldilla; Asrizal, Cynthia Wahyu; Yoo, Soo-Ji; Wisesa, Wizurai; Abdurrazaq, Abdurrazaq; Ikram, Tubagus Pasca Faiz; Ismida, Fitri Dewi; Murtadha, Raihan; Zuhra, Sofi Alfia; Ramadhani, Cut Sukma (Indonesian Journal of Case Reports, 2025)
Psoriasis vulgaris is a chronic skin inflammation characterized by the appearance of clearly limited erythematous plaques, along with rough, thick, and silvery-white scales. Systemic Lupus Erythematosus (SLE) is a multifactorial autoimmune disease with diverse clinical manifestations and can involve one or more organs. This case report presents a patient with Psoriasis Vulgaris with SLE. A 47-year-old woman presented with erythematous plaque lesions with thick scales and some hyperpigmentation, numerous, plaque-sized lesions with regional distribution on the scalp, right and left cubital areas, gluteal, left tibia, and yellow unguium dyschromia was seen on the distal lateral aspect, solitary on the right 3rd digit. Histopathological examination found typical Psoriasis Vulgaris. The patient was diagnosed with Psoriasis Vulgaris. In 2022, the patient was diagnosed with SLE and received Hydroxychloroquine sulfate therapy. The patient was treated with a combination therapy including methotrexate (MTX) and topical medications. This case highlights the importance of comprehensive evaluation for Psoriasis Vulgaris therapy with a previous history of SLE and the choice of treatment in patients with the coexistence of PV and SLE.